Single center clinical analysis of prognostic factors affecting invasive fungal rhinosinusitis - Liu, Ming; Zhang, Zhiyu; Gu, Hongbo; Zhang, Erpeng; He, Mingqiang; Shi, Lei; Shi, Guanggang (Frontiers in Surgery, 2026)
ObjectiveTo investigate the factors affecting the prognosis of invasive fungal rhinosinusitis (IFRS) by statistically analyzing clinical data collected from a single-center cohort of patients.MethodsA retrospective analysis was conducted on 43 hospitalized patients with histopathologically confirmed IFRS at Shandong Provincial Hospital between January 2019 and March 2024. Epidemiological data, clinical symptoms and signs, laboratory findings, imaging results, and treatment interventions were extracted from medical records. Clinical outcomes were followed up for over six months. Retrospective analyses were performed to identify factors influencing IFRS prognosis.ResultsA total of 43 patients were included, comprising 20 cases of acute IFRS and 23 cases of chronic IFRS. Among them, 15 patients achieved full recovery, 19 experienced sequelae, and 9 died. There were 25 males and 18 females, with a median age of 65 years (range, 24–86). Thirty-two patients (74.4%) had diabetes, and 8 patients (18.6%) had conditions associated with immunosuppression, including malignancies, autoimmune diseases. Patients with acute IFRS exhibited significantly higher C-reactive protein levels (P = 0.038) and worse prognosis (P = 0.002). Among patients who died from acute IFRS, lymphocyte counts (P = 0.003), D-dimer levels (P = 0.016), and blood glucose (P = 0.025) were markedly elevated. Orbital fungal invasion was significantly associated with the development of sequelae. Acute IFRS more frequently extended intracranially (P = 0.040), and intracranial involvement was significantly correlated with increased mortality (P = 0.004).ConclusionUnivariate analysis indicated that acute onset, immunosuppression, elevated D-dimer, lymphocyte, and blood glucose levels, as well as orbital and intracranial fungal invasion, were negative prognostic factors. Immunosuppression—including advanced age, diabetes, and hematological malignancies—was a major underlying cause of IFRS. Intracranial infection had a significant impact on mortality. Positive prognostic factors included timely and standardized systemic antifungal therapy, intrathecal antifungal administration in cases of intracranial involvement, anticoagulant treatment, prompt surgical debridement, and, when necessary, repeated surgical interventions.